Pengaruh Window Dressing Terhadap Keputusan Investasi Pada Perusahaan Lq45 Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia (2017-2021) - Mintauli Debataraja; Po. Abas Sunarya (UNIVERSITAS RAHARJA, 2023)
This study aims to prove the effect of Window Dressing on investment decisions in LQ45 companies in the banking sector on the IDX in 2017-2021. This research uses quantitative research methods. This type of research in this study uses associative research, namely research that aims to determine the relationship between two or more variables. The object of research in this research is the stock price close in December and investment decisions. Meanwhile, the subject of this research is an LQ45 company in the banking sector that is listed on the IDX in 2017-2021. The results of the study show that Window Dressing has a significant effect on investment decisions as measured by PBV and PER.